2022
DOI: 10.1007/s11920-022-01359-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Phone vs Video-Conferencing for Mental Health Treatments: A Review of the Literature

Abstract: Purpose of ReviewThe goal of this paper is to provide a comparative review of using phone (audio-only) or video for mental health treatments. Our review includes evidence of phone and video's effectiveness in terms of reduced symptomology, retention, satisfaction, therapeutic alliance, and other outcomes of interest. This review also discusses how patients and providers' experiences and attitudes differ between these two modalities. Finally, we present information on different usage rates of phone and video ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 81 publications
1
27
0
1
Order By: Relevance
“…In a project which evaluated TEL‐CBT for family caregivers of PwD, 72% of participants deemed the telephone setting very good and 27% good (Wilz & Soellner, 2016). Systematic reviews suggest that telephone‐based mental health treatments are more broadly accessible as they only require readily available equipment, have lower connection costs, and pose fewer technological challenges compared to video conferencing (Chen et al, 2022). Moreover, since many family caregivers of PwD are older and have limited experience with audiovisual communication technology, at least before the COVID‐19 pandemic (when the present study was conducted), we focus on TEL‐CBT.…”
Section: Introductionmentioning
confidence: 99%
“…In a project which evaluated TEL‐CBT for family caregivers of PwD, 72% of participants deemed the telephone setting very good and 27% good (Wilz & Soellner, 2016). Systematic reviews suggest that telephone‐based mental health treatments are more broadly accessible as they only require readily available equipment, have lower connection costs, and pose fewer technological challenges compared to video conferencing (Chen et al, 2022). Moreover, since many family caregivers of PwD are older and have limited experience with audiovisual communication technology, at least before the COVID‐19 pandemic (when the present study was conducted), we focus on TEL‐CBT.…”
Section: Introductionmentioning
confidence: 99%
“…The added visual information provided during video calls may allow providers to better assess a patient’s affect and functioning, and patients may feel more connected to their provider by seeing them as opposed to only hearing them. There is a robust literature demonstrating that video is noninferior to in-person care across a range of conditions and patient populations; there are relatively fewer rigorous studies comparing phone to in-person care, but this work has also reported comparable effectiveness between these two modalities (Chen et al, 2022; McClellan et al, 2022). A smaller, albeit growing body of literature has directly compared video and phone care and found that video care is more effective than phone in the treatment of depression, trauma, and substance use disorders (Liebmann et al, 2019; McClellan et al, 2022; Meshberg-Cohen et al, 2023).…”
mentioning
confidence: 78%
“…[13][14][15] Among internet-based interventions, mobile health (mHealth) interventions, ie, medical and public health practices supported by mobile, wireless devices, 16 offer greater freedom with regard to time and distance with the use of portable devices and fewer technical complications compared with other internet-based therapies. 17,18 However, previous meta-analyses on app-based interventions for depression have reported variable effect sizes, ranging from small [19][20][21] to medium [22][23][24] to large. 25 Notably, a 2022 systematic review and meta-analysis 26 reported significant symptom reductions associated with app interventions for anxiety but not for depression.…”
Section: Introductionmentioning
confidence: 99%
“…Amidst the challenges posed by the COVID-19 pandemic impeding conventional therapies and the upsurge of technological advances in internet devices, internet-based interventions for mental disorders have gained prominence due to their enhanced efficacy, scalability, and accessibility . Among internet-based interventions, mobile health (mHealth) interventions, ie, medical and public health practices supported by mobile, wireless devices, offer greater freedom with regard to time and distance with the use of portable devices and fewer technical complications compared with other internet-based therapies . However, previous meta-analyses on app-based interventions for depression have reported variable effect sizes, ranging from small to medium to large .…”
Section: Introductionmentioning
confidence: 99%